The Determinants of Decision-making among Polish, German and Chinese Managers in Managing a Shipping Company in China - Copp, Tomasz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2021)
Objective: The article specifies the determinants of management decision-making in the shipping industry and examines the similarities and differences in decision-making by Polish, German and Chinese managers managing a shipping company.Research Design & Methods: The research was conducted by means of direct interviews with managers from Poland, Germany and China as well as the observation of participants.Findings: HR, planning, setting priorities and delegating tasks are necessary for effective decisions, as are balance, courage and self-confidence. Cultural differences determine the decisions taken by managers from Poland, Germany and China, who will differ in the solutions that grow out of the decisions management makes. Polish managers more often refer to financial results and decision-making freedom. German managers also count the freedom to adjust their decision-making as a vital factor, as well as the ability to make quick decisions. Chinese managers, meanwhile, more frequently indicate that planning, guidelines, avoiding conflict and good cooperation are the most important factors promoting good decision-making.Implications / Recommendations: The key areas of managerial decisions in the industry include administration, finance, technology, shipping, safety and digitalisation. A manager’s character and system solutions are the most important factors in decision-making.Contribution: The comparison of Polish, German and Chinese managers in the scope of their decision making in shipping companies is a new approach to the shipping industry, one that reveals new knowledge. The results will be the basis for further research and contribute to the development of the discipline.